Domain Distribution Management of Quasi‐2D Perovskites toward High‐Performance Blue Light‐Emitting Diodes - Xia, Yu; Li, Yu‐Han; Wang, Zhao‐Kui; Liao, Liang‐Sheng (Advanced functional materials, 2023)
Quasi‐2D perovskites, as one of the promising materials applied in perovskite light‐emitting diodes (PeLEDs), have attracted great attention for their superior semiconductor properties. The inherent multiquantum well structure can induce a strong confinement effect, which is especially suitable for blue emission. However, compared to their green counterparts, blue emitters constructed from quasi‐2D perovskites are more sensitive to n domain distribution (where n represents the number of PbX6 inorganic layers). Suffering from inefficient domain distribution management, blue PeLEDs now face a variety of negative issues, including color instability, multipeak emission, and poor fluorescence yield. In this review, the development of blue PeLEDs and the optical properties of quasi‐2D perovskites are overviewed. Then, a classification and summary of strategies for domain distribution management are proposed. Finally, the challenges and potential directions of domain distribution management in quasi‐2D perovskites are summarized. This review is expected to provide a comprehensive perspective and reference on domain distribution management toward efficient blue quasi‐2D PeLEDs. Suffering from inefficient domain distribution management, the evolution of blue perovskite light‐emitting diode (PeLEDs) is relatively backward. The characteristics of quasi‐2D perovskites lead to the necessity of domain distribution management. Herein, a series of strategies, including cations with small radius, spacer cations, phosphine oxide additives, inorganic additives, solvent selection, and technological methods is detailed and summarized.